Pedagogical Consciousness Formation of Future University Educators in the Process of Teaching English - Sidash, Natalia; Roganova, Marina; Domina, Viktoriia; Victorova, Lesia; Roganov, Maxim; Miroshnichenko, Valentyna (My University, 2020)
The research is devoted to the scientific substantiation of the process of pedagogical consciousness formation of university educators in the process of teaching English, determination of the level of their pedagogical consciousness formation, developing an organization and methodological conditions for pedagogical consciousness formation, determination of the optimal methods of its diagnostics, and further implementation of organization and methodological conditions in the educational process of higher school.
Sidash Natalia. Pedagogical Consciousness Formation of Future University Educators in the Process of Teaching English / Natalia Sidash, Marina Roganova, Viktoriia Domina, Lesia Victorova, Maxim Roganov, Valentyna Miroshnichenko // Universal Journal of Educational Research. – 2020. – 8 (4). – P. 1202–1211.
Keywords: Педагогічна свідомість, майбутні викладачі вузів, викладання англійської мови, педагогічні технології; Pedagogical Consciousness, Future University Educators, Teaching English, Pedagogical Technologies; Педагогическое сознание, будущие преподаватели вузов, преподавание английского языка, педагогические технологии